Proof: Get Begin Expr Value 62
Let's prove the following theorem:
if the following are true:
- expression state at time 62 = "begin_expr"
- the expression at time 62 =
self.age
- Value Stack at time 62 = [ [ ], [ ] ]
then Value Stack at time 63 = [ [ ], [ [ ], [ ] ] ]
Proof:
Given
1 | expression state at time 62 = "begin_expr" |
---|---|
2 | the expression at time 62 = self.age |
3 | Value Stack at time 62 = [ [ ], [ ] ] |
# | Claim | Reason |
---|---|---|
1 | Value Stack at time (62 + 1) = [ [ ], Value Stack at time 62 ] | if expression state at time 62 = "begin_expr" and the expression at time 62 = self.age , then Value Stack at time (62 + 1) = [ [ ], Value Stack at time 62 ] |
2 | [ [ ], Value Stack at time 62 ] = [ [ ], [ [ ], [ ] ] ] | if Value Stack at time 62 = [ [ ], [ ] ], then [ [ ], Value Stack at time 62 ] = [ [ ], [ [ ], [ ] ] ] |
3 | Value Stack at time (62 + 1) = [ [ ], [ [ ], [ ] ] ] | if Value Stack at time (62 + 1) = [ [ ], Value Stack at time 62 ] and [ [ ], Value Stack at time 62 ] = [ [ ], [ [ ], [ ] ] ], then Value Stack at time (62 + 1) = [ [ ], [ [ ], [ ] ] ] |
4 | 62 + 1 = 63 | 62 + 1 = 63 |
5 | Value Stack at time (62 + 1) = Value Stack at time 63 | if 62 + 1 = 63, then Value Stack at time (62 + 1) = Value Stack at time 63 |
6 | Value Stack at time 63 = [ [ ], [ [ ], [ ] ] ] | if Value Stack at time (62 + 1) = Value Stack at time 63 and Value Stack at time (62 + 1) = [ [ ], [ [ ], [ ] ] ], then Value Stack at time 63 = [ [ ], [ [ ], [ ] ] ] |
Comments
Please log in to add comments